(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Planktonic foraminifera from one Atlantic Ocean (Site 397) and five Mediterranean sequences of middle to late Miocene age were investigated. The aim of the research was to refine the biostratigraphy of the Serravallian to early Tortonian interval and, since the recent literature provides no general consensus, to check the range of Neogloboquadrina acostaensis (Blow) and Paragloborotalia siakensis (Le Roy). Examination of planktonic foraminifera identified a succession of events which is, in part, new in the Mediterranean area, and documented an overlap in the distribution of N. acostaensis and P.lia siakensis. Based on the new data, the zonal scheme for the Serravallian to early Tortonian interval proposed by Iaccarino and Salvatorini (1982) and Iaccarino (1985) was emended. In particular, it was ascertained that the first occurrence (FO) of N. acostaensis falls in the upper part of the Serravallian, well before the last occurrence (LO) of P.lia siakensis. The new zonation was calibrated with the calcareous nannofossil zonation and the geomagnetic polarity time scale. In light of these new data, the events closest to the base of the Rio Castellania-Rio Mazzapiedi-Tortonian type-section are interpreted to be the LO of P.lia siakensis, the first common occurrence (FCO) of N. acostaensis, and the FO of Discoaster hamatus.. Therefore, the use of these events in selecting the GSSP of the Serravalian/Tortonian boundary is recommended.